Analysis of Factors Affecting the Use of Digital Paylater Transactions Using the Hedonic-Motivation System Adoption Model (HMSAM) - Muhammad Zahwan Latif; Rio Guntur Utomo (School of Computing, Telkom University, 2024)
The use of paylater digital transaction methods is a major trend in the current era of digitalization. This study aims to analyze the factors of Continuance Intention of paylater digital transactions. Employing a quantitative approach with Partial Least Square Structural Equation Modeling (SEM-PLS), the research focuses on individuals aged 18 and above who have made digital paylater transactions. The sampling technique chosen was a purposive sampling technique, while data collection was conducted through questionnaires. This research proposes a modified Hedonic-Motivation System Adoption Model (HMSAM) and formulates hypotheses to test the relationship between variables. Data analysis was conducted by measuring the validity and reliability of the model and applying SEM-PLS to analyze variable relationships and test hypotheses. This model integrates elements from HMSAM developed by previous researchers. The six main variables include perceived ease of use, curiosity, joy, control, satisfaction, and Continuance Intention. The results revealed that the hypothesis testing conducted for 6 from 7 hypotheses shows the value of T-Statistics> 1.96, the value of P-Values <0.05, and the value of R-Square in low and moderate indicates moderate and small classification of the influence of Factors Affecting the Use of Digital Paylater Transactions Using the Hedonic-Motivation System Adoption Model (HMSAM).